2020
DOI: 10.1093/cid/ciaa1081
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin Plus Fosfomycin Versus Daptomycin Alone for Methicillin-resistant Staphylococcus aureus Bacteremia and Endocarditis: A Randomized Clinical Trial

Abstract: Background We aimed to determine whether daptomycin plus fosfomycin provides higher treatment success than daptomycin alone for methicillin-resistant Staphylococcus aureus (MRSA) bacteremia and endocarditis. Methods A randomized (1:1) phase III superiority, open-label, and parallel group clinical trial of adult inpatients with MRSA bacteremia was conducted at 18 Spanish hospitals. Patients were randomly assigned to receive ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 31 publications
1
49
0
4
Order By: Relevance
“…In an experimental endocarditis model in rabbits, daptomycin and fosfomycin showed synergy and rapid bactericidal activity [52]. In an RCT on MRSA BSI and IE with 155 patients, treatment success rate was 12% higher for daptomycin in combination with fosfomycin compared to daptomycin monotherapy, albeit not statistically significant [53].…”
Section: Daptomycin In Infective Endocarditis and Osteomyelitismentioning
confidence: 96%
“…In an experimental endocarditis model in rabbits, daptomycin and fosfomycin showed synergy and rapid bactericidal activity [52]. In an RCT on MRSA BSI and IE with 155 patients, treatment success rate was 12% higher for daptomycin in combination with fosfomycin compared to daptomycin monotherapy, albeit not statistically significant [53].…”
Section: Daptomycin In Infective Endocarditis and Osteomyelitismentioning
confidence: 96%
“…Of the remaining 48 studies, we excluded 34 studies from the full-text evaluation for five main reasons. In total, after the full-text screening, we included 14 RCTs [13][14][15][16][24][25][26][27][28][29][30][31][32][33] in the qualitative synthesis. Of these 14 studies, 9 were multicentre studies [13-16, 24-27, 30] and 5 were single-centre studies [28,29,[31][32][33].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…In vitro laboratory data, animal models, and observational studies have suggested that combination antimicrobial therapy may be beneficial for S. aureus [8][9][10][11][12]. Over the past several years, there has been an increase in the number of randomized controlled trials (RCTs) involving patients with SAB, including the use of adjunctive rifampicin, fosfomycin, or ceftaroline for SAB [13][14][15][16]; however, the evidence supporting combination therapy in SAB is unclear. Several efforts have been made through meta-analyses to investigate whether combination antibiotic therapy is associated with better clinical outcomes than monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies demonstrate synergistic activity between daptomycin and fosfomycin, a broad-spectrum bactericidal antibiotic with activity against MRSA 47 49 . A recent open-label, multicenter, randomized clinical trial in patients with MRSA bacteremia and endocarditis compared daptomycin monotherapy (10 mg/kg per day) with the combination of daptomycin and intravenous fosfomycin (2 g every 6 hours) 50 . The protocol directed that the duration of treatment be 10 to 14 days for uncomplicated bacteremia and 28 to 42 days for complicated bacteremia.…”
Section: Other Combination Therapymentioning
confidence: 99%